2017
DOI: 10.1113/ep086311
|View full text |Cite
|
Sign up to set email alerts
|

The impact of menstrual phase on brachial artery flow‐mediated dilatation during handgrip exercise in healthy premenopausal women

Abstract: What is the central question of this study? The aim of this study was to determine the influence of menstrual phase on flow-mediated dilatation in response to sustained, exercise-induced increases in shear stress. What is the main finding and its importance? We showed, for the first time, that in healthy, premenopausal women the flow-mediated dilatation stimulated by exercise-induced increases in shear stress did not fluctuate across two phases of the menstrual cycle, despite significant fluctuations in oestro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 48 publications
(171 reference statements)
6
25
2
Order By: Relevance
“…This is inconsistent with the dominant understanding that FMD is elevated in the LF phase (Adkisson et al, 2010;Harris et al, 2012;Hashimoto et al, 1995;Kawano et al, 1996;Williams et al, 2001). In contrast to seminal investigations, and in agreement with the present findings, the majority of recent studies have not detected changes in FMD throughout the menstrual cycle in healthy young women (D'Urzo et al, 2018;Luca et al, 2016;Rakobowchuk, Parsloe, Gibbins, Harris, & Birch, 2013;Saxena, Seely, & Goldfine, 2012;Shenouda, Priest, Rizzuto, & MacDonald, 2018). Elevated FMD during the LF phase is typically attributed to a positive impact of elevated estradiol on NO bioavailability (Adkisson et al, 2010;Cicinelli et al, 1996).…”
Section: Impact Of Menstrual Phase On Fmdcontrasting
confidence: 93%
See 4 more Smart Citations
“…This is inconsistent with the dominant understanding that FMD is elevated in the LF phase (Adkisson et al, 2010;Harris et al, 2012;Hashimoto et al, 1995;Kawano et al, 1996;Williams et al, 2001). In contrast to seminal investigations, and in agreement with the present findings, the majority of recent studies have not detected changes in FMD throughout the menstrual cycle in healthy young women (D'Urzo et al, 2018;Luca et al, 2016;Rakobowchuk, Parsloe, Gibbins, Harris, & Birch, 2013;Saxena, Seely, & Goldfine, 2012;Shenouda, Priest, Rizzuto, & MacDonald, 2018). Elevated FMD during the LF phase is typically attributed to a positive impact of elevated estradiol on NO bioavailability (Adkisson et al, 2010;Cicinelli et al, 1996).…”
Section: Impact Of Menstrual Phase On Fmdcontrasting
confidence: 93%
“…Although the estradiol concentrations in the LF phase of the present study were relatively low [∼290 pmol l −1 (Table 1), despite proximity to ovulation (∼3 days prior)] overall, studies that have identified elevated FMD in the LF phase relative to the EF phase have reported similar LF estradiol levels to studies reporting no impact of phase on FMD [elevated LF FMD: ∼560 pmol l −1 (Adkisson et al, 2010;Harris et al, 2012;Hashimoto et al, 1995;Kawano et al, 1996;Williams et al, 2001) versus no phase change in FMD: ∼580 pmol l −1 (D'Urzo et al, 2018;Luca et al, 2016;Rakobowchuk et al, 2013;Saxena et al, 2012;Shenouda et al, 2018)]. Furthermore, studies…”
Section: Impact Of Menstrual Phase On Fmdsupporting
confidence: 61%
See 3 more Smart Citations